On Causality, the Modern Contract and Inertia in “Climate Migration” - Pelizza, Annalisa (Tecnoscienza – Italian Journal of Science & Technology Studies, 2023)
Commentary to the Lecture “Moving the immovable: Climate change and the multiple tensions between mobility and immobility”, by Huub Dijstelbloem (this issue).